Efektivitas Terapi Guided Imagery Dan Terapi Orientasi Realita Terhadap Gangguan Proses Berpikir (Waham) Pada Pasien Skizofrenia - Reza Aulia, Vallentina; Sholikhah, Siti; Saifudin, Moh. (Jurnal Keperawatan Muhammadiyah, 2025)
Schizophrenia is a chronic mental disorder characterized by disturbances in thought processes, one of which is delusion. Delusions are fixed false beliefs that deviate from reality and are difficult to correct, thereby impairing patients’ cognitive and social functioning. Managing delusions requires not only pharmacological treatment but also non-pharmacological approaches, such as guided imagery therapy and reality orientation therapy. This study aims to evaluate the effectiveness of both therapies in reducing delusional levels among schizophrenic patients at the Griya Cinta Kasih Foundation in Jombang Regency. The research employed a pre-experimental design using a two-group pretest– posttest approach, the sampling method used was purposive sampling. Involving 34 patients divided into two intervention groups of 17 participants each. The first group received guided imagery therapy, while the second group received reality orientation therapy. The Positive and Negative Syndrome Scale (PANSS) was used as the assessment instrument, and data were analyzed using the Mann–Whitney test. The results showed that both therapies were effective in lowering delusional scores, with a decrease from 132.94 to 105.88 in the guided imagery group, and from 135.29 to 98.65 in the reality orientation group. A p-value of 0.039 indicated a statistically significant difference, with reality orientation therapy proving to be more effective than guided imagery. In conclusion, reality orientation therapy can be considered a superior non- pharmacological intervention for reducing delusions in schizophrenic patients and may be routinely implemented in mental health nursing practice.